(N-Benzyl-N-ethyldithiocarbamato)di-tert-butylchloridotin(IV). - Abdul Mutalib, Amirah Faizah; Baba, Ibrahim; Mohamed Tahir, Mohamed Ibrahim; Tiekink, Edward R. T. (International Union of Crystallography, 2011)
The SnIV atom in the title diorganotin dithiocarbamate, [Sn(C4H9)2Cl(C10H12NS2)], is pentacoordinated by an asymmetrically coordinating dithiocarbamate ligand, a Cl and two C atoms of the Sn-bound tert-butyl groups. The resulting C2ClS2 donor set defines a coordination geometry intermediate between square pyramidal and trigonal bipyramidal with a slight tendency towards the former. In the crystal structure, C-H...[pi] contacts link centrosymmetrically related molecules into dimeric aggregates.